Ernest Hemingway's The old man and the sea - Bloom, Harold (Broomall, PA : Chelsea House, 1996)
Includes a brief biography of the author, thematic and structural analysis of the work, critical views, and an index of themes and ideas.
"A contemporary literary views book.".
Includes bibliographical references (p. 71-74) and index.
Keywords: Hemingway, Ernest, -- 1899-1961.; Hemingway, Ernest, -- 1899-1961.; American literature -- History and criticism